2020
DOI: 10.3390/medicina56030131
|View full text |Cite
|
Sign up to set email alerts
|

Yarsagumba is a Promising Therapeutic Option for Treatment of Pulmonary Hypertension due to the Potent Anti-Proliferative and Vasorelaxant Properties

Abstract: Background and objectives: Pulmonary hypertension (PH) is characterized by the vasoconstriction and abnormally proliferative vascular cells. The available allopathic treatment options for PH are still not able to cure the disease. Alternative medicine is becoming popular and drawing the attention of the general public and scientific communities. The entomogenous fungus Yarsagumba (Cordyceps sinensis) and its biologically active ingredient cordycepin may represent the therapeutic option for this incurable disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Studies have also found that C. sinensis extract and cordycepin could inhibit the proliferation of PASMC isolated from idiopathic pulmonary arterial hypertension patients. And C. sinensis extract also significantly reversed hypoxia-induced pulmonary vasoconstriction and reduced mPAP in mice (Luitel et al, 2020). Abbreviations: HPH, hypoxic pulmonary hypertension; FCP, fermented cordyceps powder; LA%, lumen area as a percentage of total vascular area; WA%, vascular wall area as a percentage of total vascular area; WT%, vascular wall thickness as a percentage of vascular outer diameter.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have also found that C. sinensis extract and cordycepin could inhibit the proliferation of PASMC isolated from idiopathic pulmonary arterial hypertension patients. And C. sinensis extract also significantly reversed hypoxia-induced pulmonary vasoconstriction and reduced mPAP in mice (Luitel et al, 2020). Abbreviations: HPH, hypoxic pulmonary hypertension; FCP, fermented cordyceps powder; LA%, lumen area as a percentage of total vascular area; WA%, vascular wall area as a percentage of total vascular area; WT%, vascular wall thickness as a percentage of vascular outer diameter.…”
Section: Discussionmentioning
confidence: 90%
“…As tumor diseases are considered a serious cause of human death all over the world, Yarsagumba is used as an antitumor agent to cure tumors (Zhou et al, 2009). The cordycepin extracted from the Yarsagumba lowers the expansion of the aortic smooth muscle cells by lowering the presence of cyclins and cyclin-dependent kinase (Luitel et al, 2020). In addition, research conducted in Sikkim, India shows that the Yarsagumba is also used to quicken corticosteroid production in different animals (Panda and Swain, 2011).…”
Section: Ophiocordyceps Sinensis and Its Production Benefits And Usagementioning
confidence: 99%
“…Another medicinal mushroom, Ophiocordyceps sinensis (OCS), known as Yarsagumba , has long been used as a folk remedy for altitude sickness, which is usually encountered above 4,000 m sea level ( 77 ). OCS enhances cardiopulmonary function and exerts therapeutic effects on fibrotic lesions and malignant tumors ( 78 , 79 ). Therefore, we examined the therapeutic effects of OCS and FTY-720 on the pathophysiology of PAH ( 45 ).…”
Section: Extracts Of Medicinal Mushroom Ophiocordyceps Sine...mentioning
confidence: 99%